Development of 3‐hydroxybutyrate dehydrogenase enzyme biosensor based on carbon nanotube‐modified screen‐printed electrode. Issue 1 (1st March 2013) - Khorsand, Fahimeh; Riahi, Siavash; Eynollahi Fard, Solmaz; Kashanian, Soheila; Naeemy, Ali; Larijani, Bagher; Omidfar, Kobra
Abstract : Precise detection of 3‐hydroxybutyrate (HB) in biological samples is of great importance for management of diabetic patients. In this study, an HB biosensor based on single‐walled carbon nanotubes (SWCNTs)‐modified screen‐printed electrode (SPE) was developed to determine the concentration of HB in serum. The specific detecting enzyme, HB dehydrogenase, was physically immobilised on SWCNTs deposited on the surface of SPEs. The electrochemical measurement of HB that involved cyclic voltammetry was based on the signal produced by β‐nicotinamide adenine dinucleotide (NADH), one of the products of the enzymatic reaction. The application of SWCNT reduced the oxidation potential of NADH to about −0.05 V. Electrochemical measurements showed that the response of this biosensor had relevant good linearity in the range of 0.1–2 mM with a low detection limit of 0.009 mM. Investigation of biosensor response in the presence of interfering molecules verified its specificity. Furthermore, the study of long‐term stability demonstrated the acceptable efficiency of this biosensor for about 100 days.